Odpowiedzi

Najlepsza Odpowiedź!
2010-03-09T00:22:46+01:00
(2x - 6)² ≤ 4x - 13
4x²-24x+36 ≤ 4x-13
4x²-24x-4x ≤ -13-36
4x² -28x ≤ -49
x²-7x ≤ -12,25

-x² + 5 ≤ 0
-x² ≤ -5
x² ≤ 5
x ≤ √5


(2x + 6x² + 1) - (2x³ - x² + 3x - 2) = 2x+6x²+1-2x³+x²-3x+2=-x+7x²+3-2x³

(x⁴ + 4x² - 3)(-3x² + x)=-3x⁶-12x⁴+9x²+x⁵+4x³-3x

(-x + 1)(3 - x²) - (x² + 2)(x + 3)=-3x+x³+3-x²-x³-3x-2x-6=-8x-3-x²
1 1 1
  • sn4p
  • Rozwiązujący
2010-03-09T00:30:12+01:00
1.
a)
(2x - 6)² ≤ 4x - 13
4x² - 24x + 36 ≤ 4x - 13
4x² - 28x ≤ -49 / : 4
x²-7x ≤ -12,25

b)
-x² + 5 ≤ 0
-x² ≤ -5
x² ≥ 5
x ≥ √5

2.
a)
(2x + 6x² + 1) - (2x³ - x² + 3x - 2) = 2x + 6x² + 1 - 2x³ + x² - 3x +2 = -2x³ + 7x² - x + 3
b)
(x⁴ + 4x² - 3)(-3x² + x) = -3x⁶ + x⁵ - 12x⁴ + 4x³ + 9x² - 3x = x(-3x⁵ + x⁴ - 12x³ + 4x² + 9x - 3)
c)
(-x + 1)(3 - x²) - (x² + 2)(x + 3) = -3x + x³ + 3 - x² - x³ - 3x² - 2x - 6 = -4x² - 5x - 3